Clinical features and histological findings are potential indicators of activity in lesions of common vitiligo. (13th December 2012) - Benzekri, L.; Gauthier, Y.; Hamada, S.; Hassam, B.
Summary Background Unstable vitiligo lesions are usually considered to be contraindications for surgical treatment. Unfortunately, in the majority of common vitiligo cases, neither accurate clinical signs nor routine blood tests are available to determine whether or not the disease is active. Objectives To establish a direct correlation between the clinical aspect of vitiligo lesions and their activity. Methods This was a prospective observational study that took place over 1 year. For each patient, a standardized evaluation included both a careful daylight and Wood's lamp examination, pictures, biopsies performed at the marginal area and histological and immunohistological studies. A second examination to assess the activity of the lesions correctly was performed 1 year after inclusion in the study. Both the clinical changes and the histological features of the lesions in actively spreading vitiligo were compared with those in stable vitiligo. Results This study included 50 patients. The lesions were classified as hypomelanotic with poorly defined borders (HPDB, 29 cases) or amelanotic with sharply demarcated borders (ASDB, 21 cases). One year after the biopsy, of the 48 patients still in the study, 20 had lesions that were considered to be stable and 28 had active lesions. Correlations were successfully obtained between clinical aspects, histological findings and vitiligo activity. The HPDB and ASDB lesions were correlated respectively with active and stable status (P < 0·001). Conclusions A simple clinical examination including a Wood's lamp examination may allow reliable and efficient evaluation of the stability of vitiligo lesions.